Sistem Tertanam Berbasis PLC pada Simulator Pemberian Label dan Pemisahan Botol - Danang Adi Nugroho; Arief Goeritno; Anang Dwi Purnomo (Ikatan Ahli Informatika Indonesia (IAII), 2021)
Utilization of photoelectric and fiberoptic sensors equipped with a number of actuators have been integrated into an embedded system based on a programmable logic controller (PLC). The labeling mechanism is based on the detection of the photoelectric sensor due to the photoelectric effect, while the bottle separation process is based on the detection of the fiberoptic sensor for two different colors. The objectives of this research includes three things, namely (i) produce a simulator controlled by a PLC system with assisted the help of sensors and actuators, (ii) create a ladder-based program structure, and (iii) measure the performance of the embedded system based on the performance of sensors and actuators. The research methods are conducted based on the research objectives through three stages, namely (i) the assembly of the conveyor frame, installation of the entire device, and integrated wiring; (ii) providing a 64-bit CX-Programmer, determining algorithms, compiling ladder, and compiling and uploading the entire program structure; and (iii) synchronization conditions and readings of on-board sensors for activation of all devices in the output line, and measurement of the processing time of stamping and bottle separation assisted by a pneumatic system. The results of the system performance during the labeling process for green and red bottles were fifteen times each, as was the case with the bottle separation process for green and red bottles, fifteen times each. The performance of the system is based on the success rate during the labeling process of 100%, while the success rate during the bottle separation process is 73.33%. The unsuccessful separation of bottles by 26.67% occurred in green bottles. The general conclusion is that a fabricated embedded system can be used as a simulator for a mechanical system of labeling and separating bottles based on bottle color.